Do eco à voz, nossa travessia: relatório técnico referente ao I encontro sobre autismo e Políticas Públicas de Sobral-Ce - Silva, Samara Fernandes da (2023)
In recent years, Autistic Spectrum Disorder (ASD) has undergone significant changes as a nosographic category. It is currently considered a neurodevelopmental disorder by the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) and is characterized by difficulties in social interaction, communication, repetitive and restricted behaviors. In the field of public policies, there is an oscillation between understanding this as a mental disorder and/or disability for legal purposes. Autistic subjects and their families have specific regulations in Brazilian legislation supported by constitutional guarantees, etc. However, the reality of care provided to them needs to be known and discussed based on their reports. Their participation in debates around the implementation of public policies is essential for them to be built and improved, especially at the municipal level, where care strategies take place on a daily basis. Therefore, our production consists of a conclusive technical advisory report regarding the organization and realization of the 1st Meeting on autism and public policies in Sobral-CE. This event was independently proposed as part of the extension actions of the Água de Chocalho project, linked to the Clinical, Subject and Public Policy Laboratory – CLIPSUS, by the Federal University of Ceará – Campus Sobral and the Professional Master’s Degree in Psychology and Public Policy – UFC – Campus Sobral and with the support of the Cearense Foundation for Scientific and Technological Development Support. In all, we had 126 direct beneficiaries (students, professionals and family members of autistic subjects who signed up and attended) and 356 indirect beneficiaries, the community surrounding these subjects. Our construction period for the event began in February 2022 and was held on October 26, 2022 from 8:00 am to 5:00 pm at the Auditorium on the Mucambinho Campus of the Federal University of Ceará, totaling 8 months of preparation, articulation with partner institutions and guests who are part of the services that assist autistic subjects and their families in the municipal setting.The program was built based on the following work axes: Municipal Care Policy for people with ASD; Comprehensive health care network for people with ASD and their families: demands and intersectoriality; Inclusive education in the school routine of people with ASD: structure and challenges; The diagnosis of ASD in the municipality of Sobralense the medicalization of childhood. For the analysis of the discussions raised, we will use the content analysis of Bardin (2016) considering the qualitative nature of the research. As a result, we were able to build three categories of analysis: Intersectoriality - The municipal care policy for people with ASD and their families; Protagonism - Health care for people with ASD; Expansion - Inclusive Education and ypur effective structure. This work has psychoanalysis as a guide regarding ethical, clinical and theoretical issues. In this sense, we hope that it will contribute to understanding the need for more actions aimed at autistic subjects and their families, among them the continuity of holding the Meetings as a proposal - together with the public authorities - that expands and integrates the alternatives of care and attention, stimulating the contact and circulation of these subjects in other spaces, places and social ties.